English women, religion, and textual production, 1500 - 1625 - White, Micheline (Women and gender in the early modern world, 2025)
Introduction: women, religious communities, prose genres, and textual production / Micheline White -- Living stones: Lady Elizabeth Russell and the art of sacred conversation / Patricia Phillippy -- Theise dearest offrings of my heart: the sacrifice of praise in Mary Sidney Herbert, Countess of Pembroke's Psalmes / Mary Trull -- Anne Dacre Howard, Countess of Arundel, and Catholic patronage / Susannah Brietz Monta -- Ensigne-bearers of Saint Clare: Elizabeth Evelinge's early translations and the restoration of England franciscanism / Jaime Goodrich -- Lady Anne Clifford and the uses of Christian warfare / Julie Crawford -- Prospecting for common ground in devotion: Queen Katherine parr's personal prayerbook / Janel Mueller -- "Halff a scrypture woman": heteroglossia and female authorial agency in prayers by Lady Elizabeth Tyrwhit, Anne Lock, and Anne Wheathill / Susan M. Felch -- Authority, scripture, and typography in Lady Grace Mildmay's manuscript meditations / Kate Narveson -- Lady Margaret Beaufort's translations as mirrors as practical piety / Brenda M. Hosington -- "Nether bitterly nor brablingly": Lady Anne Cooke Bacon's translation of Bishop Jewel's Apologia ecclesiae anglicanae / Patricia Demers